Factors Associated with COVID-19 Infection Related Multisystem Inflammatory Syndrome in Children: A Multicenter Matched Case-Control Study - Buddhaporn Prasertsakul; Phanthila Sitthikarnkha; Chetta Ngamjarus; Chaniya Jakeaw; Sumitr Sutra (Children, 2025)
Background/Objectives: After pandemic of COVID-19, there were increased the incidence of Multisystem Inflammatory Syndrome in Children (MIS-C), as reported by the Centers for Disease Control and Prevention (CDC). However, it remains unclear which specific factors link MIS-C to COVID-19 following infection. This study aims to investigate the factors associated with MIS-C in children infected with COVID-19. Methods: A multicenter-matched case-control study was conducted across Chum Phae, Khon Kaen, and Srinagarind Hospitals, Thailand. We included patients under 21 years old from those hospitals from January 2021 to February 2024. The cases were patients diagnosed with MIS-C, while the controls had a history of COVID-19 infection but had not been diagnosed with MIS-C at least 3 months post-infection. The matching criteria for cases and controls, in a 1:2 ratio, included gender and age. The association between various factors and MIS-C was examined using conditional logistic regression. Results: A total of 34 MIS-C cases were matched with 68 controls. We found that antiviral therapy administered during COVID-19 infection was linked to a reduced risk of MIS-C development, with an adjusted odds ratio of 0.06 (95% CI: 0.02–0.20). However, this study found no association between COVID-19 vaccination and nutritional status in the development of MIS-C. Conclusions: The administration of antiviral treatment during COVID-19 infection was associated with a diminished incidence of MIS-C.